Euthanasia dan Bunuh Diri Ditinjau Dari Hukum Islam Dan Hukum yang Berlaku di Indonesia - Nugroho, Irwan Budi (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2020)
This study aims to determine the causes of people committing euthanasia and suicide, knowing the Islamic legal view of euthanasia and suicide, and knowing the legal views in Indonesia regarding euthanasia and suicide. The literature study method was used in this research. After conducting the discussion, the researchers found: 1) The causes of euthanasia include: insufficient economic factors, drug prices and medical treatment costs that are too expensive and unreachable, diseases convicted of being incurable by the medical team, consideration of hospital rooms, health workers, and hospital equipment deemed usable another patient, a sense of humanity, a consideration of deserving death rather than a life of torment, and a desire to lighten the burden of the sick. 2) Personal egoism, the desire to defend others, the urge to defend certain groups, the burden of life, and burdensome regulations can cause a person to commit suicide. 3) In essence, both Islamic law and Indonesian law prohibit euthanasia and suicide.